KERJASAMA INDONESIA DENGAN INTERNATIONAL CIVIL AVIATION ORGANIZATION (ICAO) MELALUI SKEMA ICAO – DCTP 2021-2023 - Kurniawan "; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This study explains the role of ICAO as an organization under the auspices of the United Nations. Then the reason why Indonesia is collaborating with ICAO through the ICAO-DCTP scheme in the 2021-2023 range. In this case, ICAO as an international civil aviation organization ensures that each country achieves the highest possible level of safety through civil aviation regulations, procedures and navigation standards. Indonesia as a member country can achieve national interests through cooperation with ICAO. The reasons for Indonesia being the focus of this research. This study uses the theory of international cooperation. According to Dougherty & Pfaltzgraff, cooperation is carried out with the goals of each actor who has an interest so that later they meet within the scope of international relations to realize these interests. The level of analysis of this research is the nation state and qualitative research methods with bibliographical data collection techniques and interviews. The results of this study explain that the reason for Indonesia cooperating with ICAO through the ICAO – DCTP scheme is due to three reasons, 1. Indonesia Supports the ICAO SDGs Program "No Country Left Behind", 2. International Profiling of Indonesian Air Transport, 3. Indonesia's Strategy to Become Member of the ICAO Board in the 2025 Election. If Indonesia is elected as a member of the ICAO board, Indonesia can place its experts in the office of the International Civil Aviation Organization, Indonesia as a member of the council will have a direct hand in determining various policies related to international civil aviation. Keywords: ICAO, DCTP, International Cooperation, USOAP, Air Transportation, ICAO Council.